Impurity and Gender in the Hebrew Bible. - Goldstein, Elizabeth W. (Lexington Books, 2015)
Impurity and Gender in the Hebrew Bible explores the role of female blood in the Hebrew Bible and considers its theological implications for future understandings of purity and impurity in the Jewish religion.